2008
DOI: 10.1007/s00484-008-0177-0
|View full text |Cite
|
Sign up to set email alerts
|

Climate and prevalence of atopic eczema in 6- to 7-year-old school children in Spain. ISAAC PhASE III

Abstract: Atopic eczema (AE) is a chronic skin disease. Recent reports indicate that the worldwide prevalence of AE is increasing and that various environmental factors are implicated in its aetiology. Climatic conditions have been related with AE prevalence, and Spain has varying climatic conditions. The aim of this study is to document the possible climatic influence on the prevalence of AE in schoolchildren aged 6-7 years in three different climatic regions in Spain. We conducted a cross-sectional population-based su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 25 publications
5
65
0
5
Order By: Relevance
“…A 2004 epidemiological study demonstrated reduced childhood AD with higher mean annual outdoor temperature in Europe [84]. Moreover, a study of the ISAAC Phase III survey in Spain found a negative association between outdoor temperature and AD prevalence [85]. Likewise, Silverberg et al found a lower prevalence of AD in US states with higher quartile temperature [90].…”
Section: Climatementioning
confidence: 98%
See 2 more Smart Citations
“…A 2004 epidemiological study demonstrated reduced childhood AD with higher mean annual outdoor temperature in Europe [84]. Moreover, a study of the ISAAC Phase III survey in Spain found a negative association between outdoor temperature and AD prevalence [85]. Likewise, Silverberg et al found a lower prevalence of AD in US states with higher quartile temperature [90].…”
Section: Climatementioning
confidence: 98%
“…Yet, until recently, there was little evidence to support this notion. One study found that relocating children with AD from the home subarctic/temperate climate of Norway to a subtropical climate in Gran Canary for 4 weeks improved skin symptoms and quality of life [3,[83][84][85][86][87][88]. The climate in a given geographic location is determined by a combination of multiple factors, including temperature, humidity, and precipitation, as well as related factors, such as ultraviolet (UV) exposure.…”
Section: Climatementioning
confidence: 99%
See 1 more Smart Citation
“…3,22 Milk intake was also negatively associated with eczema diagnosis among Spanish primary schoolchildren. 23 Dietary intake of vitamin D was very low in our children, and virtually all (both cases and controls) ingested a lower amount than the age-and sexspecific dietary reference intake for the Chinese population (Table 4). Our data also suggested an inverse relationship between eczema severity and vitamin D intake.…”
Section: Discussionmentioning
confidence: 70%
“…En la variable climática se ha encontrado relación de asociación positiva con la latitud y negativa con la temperatura media exterior en países alejados del trópico como se ha corroborado en estudios realizados en Taiwan y España (12,13 Finlandia en el grupo de adolescentes, las frecuencias más altas de eccema se encuentran en los países que se ubican entre los trópicos de Cáncer y de Capricornio (Tablas 4 y 5) Es los países ubicados en estas zonas tropicales, como el Ecuador, los cambios de hábitos de vestido por la variación térmica, el grado de humedad ambiental (muy bajo en Quito), el estado de hidratación de la piel, la polución medioambiental, la mayor exposición a la radiación ultravioleta (¿de los trópi-cos? ), pueden favorecer sensibilizaciones mediadas por IgE (14)(15)(16).…”
Section: Discusión Y Conclusionesunclassified